GAME-CHANGING LEARNING: HOW DIGITAL GAMES BOOST LEARNING ENGAGEMENT - Hendri Yawan; Marhamah Marhamah; Hariadi Syam (Sanata Dharma University Yogyakarta, 2025)
The research examines how Digital Game-Based Learning (DGBL) offers some advantages for secondary school students’ Engagement in the EFL classroom in Indonesia. It also investigates some drawbacks encountered during DGBL implementation and provides refutations to disprove the counterarguments. The methodology undertaken is a synthesis research methodology. Relevant literature was obtained through peer-reviewed articles from reliable journals such as Google Scholar, ERIC, ProQuest Education Journal, and other relevant sources. The findings further reveal that teaching EFL classrooms under the framework of DGBL benefits students in three ways. Firstly, digital games can engage students’ emotions in the learning process by promoting a psychological state that is commonly known as a flow condition. It refers to playing a digital game with fun, interest, and deep concentration. Secondly, DGBL can engage students’ cognition by providing problem-solving activities that help students think critically to decipher the challenges of the games. Lastly, DGBL can also promote behavioral engagement by situating students in cooperative learning activities, which, with guidance from teachers, encourage students to participate collaboratively as a team during the gameplay. In this study, the investigation only focuses on which aspects of DGBL can significantly leverage students’ engagement in the EFL learning classroom. Therefore, further analysis is required to examine how DGBL can be an effective instructional strategy to meet the English standard competencies in the Indonesian national curriculum.